Germline Predisposition to Myeloid Neoplasms in Inherited Bone Marrow Failure Syndromes, Inherited Thrombocytopenias, Myelodysplastic Syndromes and Acute Myeloid Leukemia: Diagnosis and Progression to Malignancy - Kansal, Rina (Journal of Hematology Research, 2021)
The diagnosis of any genetic predisposition to any malignancy carries profound significance for the patient and the family, with implications for clinical management that differ from when there is no identifiable heritable cause. The presence of a genetic predisposition to develop hematologic neoplasms is under-recognized. Therefore, such genetic predisposition was added as a separate diagnosis in the diagnostic World Health Organization classification in 2016. Such genetic predisposition may occur in the absence of syndromic or physical signs; even a familial history may be absent in some individuals. Also, currently, surveillance guidelines for individuals who may harbor such a genetic predisposition but have not developed a malignancy are mostly limited to expert opinion. The application of genomic sequencing methods in clinical laboratories has allowed increased recognition of such germline predisposition. Very recently, evidence is beginning to emerge that sheds light on possible steps for progression to a myelodysplastic syndrome or acute myeloid leukemia. This article provides an overview of the clinical aspects of the inherited forms of bone marrow failure syndromes, myelodysplastic syndromes, and acute myeloid leukemia, including for germline mutated CEBPA, RUNXI, ANKRD26, ETV6, DDX41, GATA2, and SAMD9/9L genes. Considerations for diagnosis are discussed for individuals and families who harbor a genetic or familial predisposition to developing a myeloid malignancy with future perspectives.